(untitled) (Journal of Production Engineering, 1992)
The development of computers and contemporary machine tools, as well as machine tools based on computers, has enabled the establishment of computer-integrated manufacturing systems (CIM). True computer-integrated manufacturing involves the automation, computerization, and increased intelligence of all aspects of manufacturing processes and many connections between factory processes. Many non-automated links between these processes traditionally rely on human judgment, experience, and intuition, which are naturally challenging tasks to automate. However, the emergence of artificial intelligence, specifically expert systems, has made it possible to automate these links. This paper provides a brief overview of the model of the processor and computer programs designed for measuring and inspection operations based on the principles of building expert systems. This processor is part of a complex system for the automatic projection and programming of Flexible Manufacturing Systems (FMS) for processing rotational parts. The development of this complex system began several years ago at the Institute for Production Engineering of the Faculty of Technical Sciences in Novi Sad